2010
DOI: 10.1097/00007890-201007272-01957
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Vascular Endothelial Growth Factor Production and Its Effect on Revascularization and Function of Graft Islets in Diabetic Rats

Abstract: AIM: To determine whether the elevated vascular endothelial growth factor (VEGF) expression produced by the transfected vascular endothelial cells (VECs) could stimulate angiogenesis of the graft islets and exert its effect on the graft function. CONCLUSION: Elevated VEGF production by transfected vascular endothelial cells in the site of islet transplantation stimulates angiogenesis of the islet grafts. The accelerated islet revascularization in early stage could improve the outcome of islet transplantation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This study confirmed the key role of VEGF in the improvement of islet engraftment efficiency (3,46,53). Several authors have thus focused on developing strategies to overexpress VEGF in pancreatic islets using viral infection (6,7). However, VEGF is efficiently overexpressed by adenoviral infection (6,12), but there are several obstacles or safety risks associated with gene therapy, such as the transduction of unwanted cells, which is particularly relevant here, thus requiring fine-tuned transgene expression.…”
Section: Discussionmentioning
confidence: 99%
“…This study confirmed the key role of VEGF in the improvement of islet engraftment efficiency (3,46,53). Several authors have thus focused on developing strategies to overexpress VEGF in pancreatic islets using viral infection (6,7). However, VEGF is efficiently overexpressed by adenoviral infection (6,12), but there are several obstacles or safety risks associated with gene therapy, such as the transduction of unwanted cells, which is particularly relevant here, thus requiring fine-tuned transgene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our results indicate that regulated overexpression of hVEGF in a hypoxia-inducible manner enhances islet vascular engraftment and preserves islet function overtime in transplants. transfer strategies have been investigated [10][11][12][13][14][15][16][17][18]. Among the angiogenic genes, delivery of vascular endothelial growth factor (VEGF) to islets using adenoviral vectors or nonviral carriers [13][14][15][16][17][18] has been shown to increase the survival of transplanted islets.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recently it has been reported that in animal models MSCs are able to enhance survival and function of islet graft not only by immune modulation mechanisms (5) but also by increasing islet revascularization (20). In detail, MSCs secrete cytokines like vascular endothelial growth factor (VEGF) and hepatocyte growth factor (HGF), which are able both to protect endocrine and endothelial islet cells after isolation and to increase islet revascularization after transplant (8, 11, 14, 33).…”
Section: Introductionmentioning
confidence: 99%